Risk factors for surgical site infection following lumbar spinal surgery: a meta-analysis - Zhang L; Li EN (Dove Medical Press, 2018)
Lin Zhang, Er-Nan Li Department of Spine Surgery, Beijing Shijitan Hospital, Capital Medical University, Beijing, China Objective: To identify risk factors for surgical site infection (SSI) in patients who had undergone lumbar spinal surgery.Methods: Studies published in PubMed, Web of Science, and Embase were systematically reviewed to determine risk factors for SSI following lumbar spinal surgery. Results are expressed as risk ratios (RRs) with 95% CIs and weighted mean difference (WMD) with 95% CI. A fixed-effect or random-effect model was used to pool the estimates according to heterogeneity among the studies included.Results: Sixteen studies involving 13,393 patients were included in this meta-analysis. Pooled estimates suggested that diabetes (RR 2.19, 95% CI 1.43–3.36; P<0.001), obesity (RR 2.87, 95% CI 1.62–5.09; P<0.001), BMI (WMD 1.32 kg/m2, 95% CI 0.39–2.25; P=0.006), prolonged operating time (WMD 24.96 minutes, 95% CI 14.77–35.15; P<0.001), prolonged hospital stay (WMD 2.07 days, 95% CI 0.28–3.87; P=0.024), hypertension (RR 1.28, 95% CI 1.08–1.52; P=0.005), and previous surgery (RR 2.06, 95% CI 1.39–3.06; P<0.001) were independent risk factors for SSI in patients who had undergone lumbar spine surgery. Current smoking (RR 0.89, 95% CI 0.75–1.06; P=0.178), American Society of Anesthesiologists grade >2 (RR 2.63, 95% CI 0.84–8.27; P=0.098), increased age (WMD 1.43 years, 95% CI -1.15 to 4.02; P=0.278), COPD (RR 1.21, 95% CI 0.68–2.17; P=0.521), cardiovascular disease (RR 1.63, 95% CI 0.40–6.70; P=0.495), rheumatoid arthritis (RR 1.76, 95% CI 0.53–5.90; P=0.359), and osteoporosis (RR 1.91, 95% CI 0.79–4.63; P=0.152) were not risk factors for postoperative SSI.Conclusion: Our results identified several important factors that increased the risk of postoperative SSI. Knowing these risk factors, surgeons could adequately analyze and evaluate risk factors in patients and then develop prevention measurements to reduce the rate of SSI. Keywords: lumbar spinal surgery, surgical site infection, risk factors, meta-analysis